MEDIA ROLES IN HARNESSING ART FOR PEACE BUILDING IN IMPROVING SOCIO-CULTURAL COMMUNITY LIFE - Silas Oghenemaro Emovwodo (Universitas Sebelas Maret, 2017)
The United Nations Universal Declaration of Human Rights, 1948, Article 27, Part 1 states: Everyone has the right freely to participate in the cultural life of the community, to enjoy the arts and to share in scientific advancement and its benefits. Art- film, music, painting, dance- can be a way to approach peace and reconciliation. Whether it be a way of expressing the emotions created by conflict, a piece of public art which commands attention or a community project bringing together affected and even warring participants, the arts can offer a creative and non-political means to engage communities in projects of peace and reconciliation. Peace building cuts across disciplines; however the field of the arts often receives less attention. Given the complexities of conflict and violence there is need to adopt diverse tactics that meet the challenges posed during peace building. Because there is little documentation of how art creates social and personal change, this paper will highlight how media can harness art for peace building and sustenance to improve socio-cultural community life.